DAFTAR ISI - Jurnal Kimia, Jurnal Kimia (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016, 2016)
JURNAL KIMIA ( JOURNAL OF CHEMISTRY ) ISSN 1907-9850 VOLUME 10 , NOMOR 1, JANUARI 201 6